39.4k views
1 vote
12. Simplify –3√ 2 + 3√ 8 .

A. 3√ 2
B. –3√ 2
C. 0
D. 9√ 2

User Laertiades
by
5.9k points

2 Answers

4 votes
The answer is: [A]: 3√ 2 .
______________________________
Step-by-step explanation:
______________________________
Simply: -3√ 2 + 3√ 8 ;
_______________________________

Let us simplify: 3√ 8 ;
________________________________________________
Let us simplify:
________________________________________________
√ 8 ; → √ 8 = √ 4 * √ 2 = 2√ 2 ;
________________________________________________

→ √ 8 = √ 4 * √ 2 = 2√ 2 ;
__________________________________

→ 3√ 8 = 3 * 2√ 2 = 6√ 2 ;
____________________________________________________
So, rewrite the original problem, substituting: "6
√ 2" for "3√ 8" ;
____________________________________________________

-3√ 2 + 3√ 8 =
____________________________________________________

-
3√ 2 + 6√ 2 = 3√ 2 ; which is Answer choice: [A].
____________________________________________________
User Lou Alicegary
by
6.0k points
1 vote
Your answer would be, A. 3√ 2. Hope I helped you :)
User Saurel
by
5.6k points